Abnormal distribution of GABAA receptors in brain of duchenne muscular dystrophy patients. Issue 4 (3rd January 2017) - Suzuki, Yuji; Higuchi, Shinya; Aida, Izumi; Nakajima, Takashi; Nakada, Tsutomu
ABSTRACT: Introduction: In this study we sought to: (1) determine the distribution of GABAA receptors (GABAA ‐Rs) in the brain of Duchenne muscular dystrophy (DMD) patients; and (2) ascertain if the distribution pattern correlates with cognitive dysfunction. Methods: Fourteen DMD patients [young adult ( n  = 7, 18–25 years old) and older adult ( n  = 7, 30–37 years old) groups] and 16 age‐matched normal volunteers participated. GABAA ‐R distribution was assessed using 123 I‐IMZ‐SPECT. Neuropsychological assessments were performed using 3 different test batteries, the WAIS‐III, WMS‐R, and Wisconsin Card Sorting Test (WCST). Results: All DMD patients showed significant decline in 123 I‐IMZ uptake in the prefrontal cortex ( P  < 0.05). Although no differences were detected in the WAIS‐III and WMS‐R, the WCST scores of DMD patients (2.8 ± 1.9) were significantly lower ( P  < 0.01) than those of normal volunteers (5.4 ± 0.7). Both abnormalities were more pronounced in older adult patients. Conclusion: The findings demonstrate that DMD is accompanied by a reduction in the prefrontal cortex distribution of GABAA ‐Rs. Muscle Nerve 55 : 591–595, 2017